2013
DOI: 10.1002/chir.22194
|View full text |Cite
|
Sign up to set email alerts
|

An Enantiospecific Polyene Cyclization Initiated by an Enantiomerically Pure Bromonium Ion

Abstract: Dimethylaluminum triflate-mediated activation of tetrafluorobenzoates of enantiomerically pure bromohydrins results in enantiospecific polyene cyclizations. The initiation of cyclization by enantiomerically pure bromonium ions and subsequent propagation is not subject to catastrophic erosion of enantiomeric purity by any intramolecular or intermolecular bromonium ion-to-alkene transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 90 publications
(120 reference statements)
0
13
0
2
Order By: Relevance
“…The main product was now indeedt he fully cyclized 9a.H owever,i tw as accompanied by small amountso fac omplex mixture of minor byproducts.P urification by column chromatography enabled the isolation of the main cyclization product 9a with about 90 % purity in good yield of 64 %( Table 1, entry 1). [25] 2-BArF was also used to cyclize alkenyl-substituted aromatics. The relative configuration of 9a could be established by X-ray structure analysis.…”
Section: Bromiranium-induced Polyene Cyclizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main product was now indeedt he fully cyclized 9a.H owever,i tw as accompanied by small amountso fac omplex mixture of minor byproducts.P urification by column chromatography enabled the isolation of the main cyclization product 9a with about 90 % purity in good yield of 64 %( Table 1, entry 1). [25] 2-BArF was also used to cyclize alkenyl-substituted aromatics. The relative configuration of 9a could be established by X-ray structure analysis.…”
Section: Bromiranium-induced Polyene Cyclizationsmentioning
confidence: 99%
“…Again, crystallizationf rom acetone led to pure product in lower overall yield (30 %). [25] 2-BArF was also used to cyclize alkenyl-substituted aromatics. Following the standard procedure, alkene 11 was reacted to give 12 as the main product in 34 %y ield (Scheme 6).…”
Section: Bromiranium-induced Polyene Cyclizationsmentioning
confidence: 99%
“…[61] Acetolysis experiments showed that the chiral bromiranium ion derived from enantioenriched bromo tosylate 24 can be captured with high enantiospecificity in the absence of alkenes. [62] However, the inclusion of (E)-4-octene 26 as an additive severely eroded the selectivity (Scheme 28). Thee xtent of erosion depends on the concentrations of the alkene and the nucleophile,a sw ell as the identity of the counterion.…”
Section: S E Denmark Et Almentioning
confidence: 99%
“…The reaction mixture was quenched with 1.0 M aq HCl solution, extracted with EtOAc, washed with saturated NaHCO 3 solution, brine, dried over MgSO 4 , and concentrated in vacuo to give 7 (9.4 g, quant) as a colorless oil which was used directly without purification. The spectroscopic data are in accordance with the literature values reported …”
Section: Methodsmentioning
confidence: 99%